Discover a world of knowledge at Westonci.ca, where experts and enthusiasts come together to answer your questions. Connect with a community of experts ready to help you find accurate solutions to your questions quickly and efficiently. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the expression [tex]\(\sqrt[3]{27 x^{-3}}\)[/tex], follow these steps:
1. Understand the expression: We need to find the cube root of [tex]\(27 x^{-3}\)[/tex].
2. Simplify the expression inside the cube root:
- We start with [tex]\(27 x^{-3}\)[/tex].
- Recall the property of exponents: [tex]\(a^{-n} = \frac{1}{a^n}\)[/tex]. Hence, [tex]\(x^{-3} = \frac{1}{x^3}\)[/tex].
- Substituting this back, we get [tex]\(27 x^{-3} = 27 \cdot \frac{1}{x^3} = \frac{27}{x^3}\)[/tex].
3. Find the cube root:
- We now need to find the cube root of [tex]\(\frac{27}{x^3}\)[/tex].
- The cube root of a fraction is the fraction of the cube roots: [tex]\(\sqrt[3]{\frac{27}{x^3}} = \frac{\sqrt[3]{27}}{\sqrt[3]{x^3}}\)[/tex].
4. Calculate the cube roots:
- [tex]\(\sqrt[3]{27} = 3\)[/tex] since [tex]\(3^3 = 27\)[/tex].
- [tex]\(\sqrt[3]{x^3} = x\)[/tex] since the cube root and cube cancel each other out.
5. Put it all together:
- Combining these, we get [tex]\(\frac{3}{x}\)[/tex].
6. Substitute the given value of [tex]\(x\)[/tex]:
- According to the given answer, [tex]\(x = 1\)[/tex].
7. Determine the final result:
- Substituting [tex]\(x = 1\)[/tex], we get [tex]\(\frac{3}{1} = 3\)[/tex].
Therefore, the value of [tex]\(\sqrt[3]{27 x^{-3}}\)[/tex] when [tex]\(x = 1\)[/tex] is [tex]\(3\)[/tex].
1. Understand the expression: We need to find the cube root of [tex]\(27 x^{-3}\)[/tex].
2. Simplify the expression inside the cube root:
- We start with [tex]\(27 x^{-3}\)[/tex].
- Recall the property of exponents: [tex]\(a^{-n} = \frac{1}{a^n}\)[/tex]. Hence, [tex]\(x^{-3} = \frac{1}{x^3}\)[/tex].
- Substituting this back, we get [tex]\(27 x^{-3} = 27 \cdot \frac{1}{x^3} = \frac{27}{x^3}\)[/tex].
3. Find the cube root:
- We now need to find the cube root of [tex]\(\frac{27}{x^3}\)[/tex].
- The cube root of a fraction is the fraction of the cube roots: [tex]\(\sqrt[3]{\frac{27}{x^3}} = \frac{\sqrt[3]{27}}{\sqrt[3]{x^3}}\)[/tex].
4. Calculate the cube roots:
- [tex]\(\sqrt[3]{27} = 3\)[/tex] since [tex]\(3^3 = 27\)[/tex].
- [tex]\(\sqrt[3]{x^3} = x\)[/tex] since the cube root and cube cancel each other out.
5. Put it all together:
- Combining these, we get [tex]\(\frac{3}{x}\)[/tex].
6. Substitute the given value of [tex]\(x\)[/tex]:
- According to the given answer, [tex]\(x = 1\)[/tex].
7. Determine the final result:
- Substituting [tex]\(x = 1\)[/tex], we get [tex]\(\frac{3}{1} = 3\)[/tex].
Therefore, the value of [tex]\(\sqrt[3]{27 x^{-3}}\)[/tex] when [tex]\(x = 1\)[/tex] is [tex]\(3\)[/tex].
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.